2016
DOI: 10.1093/jac/dkw464
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerance of dolutegravir-based combined ART in perinatally HIV-1-infected adolescents: a French multicentre retrospective study

Abstract: Dolutegravir was safe and virologically effective in these patients, for whom multiple interventions were required to improve compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 8 publications
4
27
0
Order By: Relevance
“…These rates were similar to those reported in virologically suppressed adults enrolled in the European AIDS Treatment Network (NEAT) 022 trial, in which 93.1% of individuals switching from a ritonavir‐boosted PI to a dolutegravir‐based regimen maintained virological suppression at week 48 . Similarly, previous paediatric cohort studies, involving mainly adolescents and youths, reported high rates of sustained virological success among treatment‐experienced paediatric and young adult patients with viral suppression at dolutegravir initiation . We herein report that similar rates of viral success can be obtained among the three age groups of paediatric and young adult patients, even in the youngest children.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…These rates were similar to those reported in virologically suppressed adults enrolled in the European AIDS Treatment Network (NEAT) 022 trial, in which 93.1% of individuals switching from a ritonavir‐boosted PI to a dolutegravir‐based regimen maintained virological suppression at week 48 . Similarly, previous paediatric cohort studies, involving mainly adolescents and youths, reported high rates of sustained virological success among treatment‐experienced paediatric and young adult patients with viral suppression at dolutegravir initiation . We herein report that similar rates of viral success can be obtained among the three age groups of paediatric and young adult patients, even in the youngest children.…”
Section: Discussionsupporting
confidence: 87%
“…Dolutegravir was well tolerated. The low rate of severe drug‐related adverse events is similar to those previously reported in adults , adolescents and children but lower than that reported in an adult cohort study, in which 13.7% of individuals stopped taking dolutegravir because of intolerability .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Studies focusing on the efficacy of dolutegravir‐containing regimens to treat teenagers are scarce and generally had small samples . In our study, a subgroup multivariable analysis restricted to patients aged 13 to 24 years included 21,271 patients and confirmed the findings shown in the overall sample analysis.…”
Section: Resultssupporting
confidence: 82%